Difluorinated Curcumin: A Promising Curcumin Analogue with Improved Anti-Tumor Activity and Pharmacokinetic Profile - Abbas Momtazi, Amir; Sahebkar, Amirhossein (Current Pharmaceutical Design, 2016)
Background: Curcumin, a polyphenol from turmeric, is a dietary phytochemical with a diversity of health benefits including strong anti-tumor effects. Curcumin undergoes a rapid metabolism resulting in a low oral bioavailability. 3, 4-difluorobenzylidene curcumin or (CDF) is a novel fluorinated curcumin analogue which has been shown to be about 3 times more bioavailable than curcumin. This review aimed to summarize the findings of studies related to pharmacokinetic and pharmacological characteristics of CDF. Methods: A systematic literature search was prformed in Scopus and Medline to identify all published articles dealing with CDF. Results: Biodistribution assays have revealed that curcumin is mostly distributed to the heart and lung tissues while CDF is preferentially accumulated in pancreas where its tissue concentrations reach two folds higher than that of curcumin. Moreover, CDF has been reported to possess stronger cytotoxic effects compared with CMN in both monolayer and spheroid cultures of different tumor cell lines including chemo-resistant ones. CDF can promote tumor suppression through multiple mechanisms including inhibition of self-renewal capacity of cancer stem/stem-like cells, clonogenicity invasiveness and angiogenesis of tumor cells, while increasing the sensitivity of cells to chemotherapy. These effects are the results of the modulatory action of CDF on diverse targets, such as miRNAs (miR-21, miR-101, miR-210, miR34a and miR34c), PTEN, CD44, EGFR, EpCAM, EZH2, HIF-1α, and VEGF. Conclusion: This review presents an overview of the findings on metabolism and pharmacological activities of CDF, and also highlights potential opportunities to use this novel curcumin analogue in the treatment of cancer.
Keywords: fluorination